[PP.35.14]: EGG WHITE HYDROLYSATE PREVENTS VASCULAR EFFECTS CAUSED BY CHRONIC EXPOSURE TO LOW CONCENTRATIONS OF MERCURY. (June 2015) - Rizzetti>, D.>; Fernandez, F.; Moreno, S.; Vera, G.; Lopez-Miranda, V.; Peçanha, F.; Vassallo, D.; Miguel, M.; Wiggers, G.
Abstract : Objective: The aim of our study was to investigate the potential beneficial effects of dietary supplementation with egg white protein hydrolysate obtained after enzymatic hydrolysis with Pepsin, with in vitro antioxidant activity, on the vascular effects caused by chronic intoxication by low concentrations of mercury (Hg). Design and method: Four groups of 8-week-old Wistar male rats (200 g) were treated for 60 days with: a) Control (saline solution, i.m.); b) Mercury (HgCl2) - mercury chloride (1st dose 4.6 mg/kg, subsequent doses 0.07 mg/kg/day, i.m., to cover daily loss, using the model described by Wiggers et al., 2008); c) Egg White Hydrolysate from Pepsin BC for 8 hours (1 g/kg/day, gavage, according to model describe by Miguel et al., 2007); d) Mercury plus Egg White Hydrolysate. Sistolic (SBP) and Diastolic (DBP) Blood Pressure were assessed invasively through the carotid artery cannulation. The vascular reactivity experiments were performed in an organ bath, where we analyzed the vasoconstrictor response to phenylephrine (PHE) in the presence and absence of endothelium, in the presence of NOS inhibitor (L-NAME), non-selective COX inhibitor (indomethacin), selective COX-2 inhibitor (NS 398), NADPH oxidase inhibitor (apocynin) and superoxide dismutase (SOD). Data were analyzed by Analysis of Variance (ANOVA) followed by a Bonferroni test. Results: Hg treatment resulted in 1) an increased in SBP and aortic vasoconstrictor response to PHE; 2) the increased involvement of ROS from NADPH oxidase and constrictor prostanoids, mainly from COX-2 in response to PHE, whereas the endothelial NO modulation of such responses was reduced. Treatment with egg white hydrolysate prevented the increased in SBP and PHE responses elicited by Hg in aorta. In addition, it increased the NO modulation of vasoconstrictor responses and reduced the ROS and prostanoids from COX-2 participation in the increase of PHE responses by Hg. Conclusions: Mercury increases the SBP and vasoconstrictor response to PHE by reducing NO bioavailability and increasing the involvement of ROS and vasoconstrictor prostanoids from COX-2. Egg white hidrolisate protects against the deleterious effects caused by metal, demonstrating a beneficial therapeutic potential.